2020
DOI: 10.1111/echo.14579
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiographic parameters differentiating heart failure with preserved ejection fraction from asymptomatic left ventricular diastolic dysfunction

Abstract: Background (LVDD) either remains latent or manifests as heart failure with preserved ejection fraction (HFpEF). Little is known about echocardiographic parameters associated with symptomatic phenotype. Objective To investigate echocardiographic parameters associated with symptomatic state in LVDD. Methods Three hundred and thirty patients with definite diagnosis of LVDD (according to ASE/EACVI recommendations 2016) were included and divided into asymptomatic LVDD and HFpEF groups according to presence of dyspn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…It has been recently shown that DD and low e' are independent predictors of subclinical coronary artery calcification 34. Also, it has been recently reported that low e' lateral can be associated with symptom status in those with LVDD defined by 2016 ASE criteria, with e' lateral negatively correlating with NYHA class in preserved LVEF 35. One or more abnormal echocardiographic markers was found in a majority of an asymptomatic group at low-to-intermediate risk for CAD; few in this group were identified echocardiographically as having DD 36.…”
mentioning
confidence: 98%
“…It has been recently shown that DD and low e' are independent predictors of subclinical coronary artery calcification 34. Also, it has been recently reported that low e' lateral can be associated with symptom status in those with LVDD defined by 2016 ASE criteria, with e' lateral negatively correlating with NYHA class in preserved LVEF 35. One or more abnormal echocardiographic markers was found in a majority of an asymptomatic group at low-to-intermediate risk for CAD; few in this group were identified echocardiographically as having DD 36.…”
mentioning
confidence: 98%
“…LV diastolic cardiac function was assessed as early diastolic tissue velocity (e’). We defined systolic dysfunction as LAS ≤13.7% and diastolic dysfunction as e’ ≤8.2 cm/second, which are median—2SD of control values [ 27 ]. LV cardiac dysfunction was defined as occurrence of systolic and/or diastolic dysfunction.…”
Section: Methodsmentioning
confidence: 99%
“…4 Echocardiography allows noninvasive diagnosis of early diastolic dysfunction. [5][6][7][8] However, echocardiography and in particular tissue doppler imaging remain expensive and are not considered to be a wide screening method for asymptomatic patients. As electrical and mechanical functions of cardiac performance are closely coupled, advanced signal processing and machine learning methods have been used to identify subtle alterations in a 12-lead electrocardiogram (ECG) in patients who were referred for coronary computed tomography.…”
Section: Introductionmentioning
confidence: 99%